Highly N‐doped carbon with low graphitic‐N content as anode material for enhanced initial Coulombic efficiency of lithium‐ion batteries - Tang, Yihua; Chen, Jingjing; Mao, Zhiyong; Roth, Christina; Wang, Dajian (Carbon energy, 2023)
N‐doped carbons as one of the most prominent anode materials to replace standard graphite exhibit outstanding Li+ storage performance. However, N‐doped carbon anodes still suffer from low N‐doping levels and low initial Coulombic efficiency (ICE). In this study, high N‐doped and low graphitic‐N carbons (LGNCs) with enhanced ICE were synthesized by taking advantage of a denitrification strategy for graphitic carbon nitride (g‐C3N4). In brief, more than 14.5 at% of N from g‐C3N4 (55.1 at% N) was retained by reacting graphitic‐N with lithium, which was subsequently removed. As graphitic‐N is largely responsible for the irreversible capacity, the anode's performance was significantly increased. Compared to general N‐doped carbons with high graphitic‐N proportion (>50%) and low N content (<15 at%), LGNCs delivered a low proportion of 10.8%–17.2% within the high N‐doping content of 14.5–42.7 at%, leading to an enhanced specific capacity of 1499.9 mAh g−1 at an ICE of 93.7% for the optimal sample of LGNC (4:1). This study provides a facile strategy to control the N content and speciation, achieving both high Li+ storage capacity and high ICE, and thus promoting research and application of N‐doped carbon materials. High N‐doped (14.5–42.7 at%) carbon with low graphitic‐N proportion (10.8%–17.2%) has been fabricated by denitrification for graphitic carbon nitride (g‐C3N4) using Li metal powder as both reductant and prelithiation reagent. As anode materials for lithium batteries, the optimal sample exhibits a high capacity of 1499.9 mAh g−1 with an enhanced ICE of 93.7%.